Porcine Endogenous Retrovirus (PERV) and its Transmission Characteristics: A Study of the New Zealand Designated Pathogen-Free Herd - O. Garkavenko; S. Wynyard; D. Nathu; D. Simond; M. Muzina; Z. Muzina; L. Scobie; R. D. Hector; M. C. Croxson; P. Tan; B. R. Elliott (Cell Transplantation, 2008)
Previously a strategy for monitoring of pigs intended for cell transplantation was developed and successfully applied to several representative herds in New Zealand. A designated pathogen-free (DPF) herd has been chosen as a good candidate for xenotransplantation. This herd has previously tested free of infectious agents relevant to xenotransplantation and we present here an in depth study of porcine endogenous retrovirus (PERV) transmission. A panel of assays that describes the constraints for the transmission of PERV has been suggested. It includes a) infectivity test in coculture of DPF pig primary cells with both human and pig target cell lines; b) RT activity in supernatant of stimulated primary cells from DPF pigs; c) viral load in donor's blood plasma; d) PERV proviral copy number in DPF pig genome; e) PERV class C prevalence in the herd and its recombination potential. There was no evidence of PERV transmission from DPF pig tissue to either pig or human cells. Additionally, there was no evidence of PERV RNA present in pig blood plasma. PERV copy number differs in individual pigs from as low as 3 copies to 30 copies and the presence of PERV-C varied between animals and breeds. In all DPF pigs tested, a specific locus for PERV-C potentially associated with the recombination of PERV in miniature swine was absent. Presented data on the PERV transmission allows us to classify the DPF potential donors as “null” or noninfectious pigs.